1989
DOI: 10.1002/jemt.1060120208
|View full text |Cite
|
Sign up to set email alerts
|

Application of an ultrahigh‐resolution scanning electron microscope (UHS‐T1) to biological specimens

Abstract: In 1985 we developed an ultrahigh-resolution scanning electron microscope with a resolution of 0.5 nm. It is equipped with a field emission gun and an objective lens with a very short focal length. In this study we report a survey of some different preparation techniques and biological specimens using the new scanning electron microscope. Intracellular structures such as cell organelles were observed surprisingly sharper than those observed by ordinary scanning electron microscopes. However, at magnifications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 12 publications
1
28
0
Order By: Relevance
“…The presence of pores in the GBM has been postulated from physiological studies [I] and demonstrated by transmission electron microscopy (TEM) by us [2][3] and others [4][5][6], Although scanning electron microscopy (SEM) has an advantage over TEM in that topographical dissimilarity can be observed three-dimensionally, it failed to demonstrate the presence of pores in the GBM.In 1985, a new type of SEM, the ultrahighresolution SEM (HSEM), was developed by Tanaka et al [7]. It is equipped with a field emission source and an objective lens of very short focal length, and has a resolving power of 0.5 nm at 30 kV.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of pores in the GBM has been postulated from physiological studies [I] and demonstrated by transmission electron microscopy (TEM) by us [2][3] and others [4][5][6], Although scanning electron microscopy (SEM) has an advantage over TEM in that topographical dissimilarity can be observed three-dimensionally, it failed to demonstrate the presence of pores in the GBM.In 1985, a new type of SEM, the ultrahighresolution SEM (HSEM), was developed by Tanaka et al [7]. It is equipped with a field emission source and an objective lens of very short focal length, and has a resolving power of 0.5 nm at 30 kV.…”
mentioning
confidence: 99%
“…Therefore, HSEM theore tically enables imaging of biological speci mens up to macromolecular resolution, if they are adequately prepared. Recently, intramembranous particles [8], macromolecules including ferritin and ribosome [7] have been visualized with HSEM. We, therefore, em ployed HSEM to investigate the ultrastruc ture of GBM in situ.…”
mentioning
confidence: 99%
“…High-resolution scanning electron microscopy, devised by Tanaka et al [24], is equipped with a field emission source and objective lens of very short focal length and resolving power of 0.5 nm at 30 kV. We demonstrated the polygonal meshwork structure composed of strands and pores in the GBM with high-resolution scanning electron microscopy after tannin-osmium conductive staining [13][14][15] instead of the conventional metal coating.…”
Section: Discussionmentioning
confidence: 85%
“…One must be carefitl in defining what resolution can be at the impact point of the beam. In addition, the probe size obtained becaitse the separation of 2 points in a highly spewill become s~naller with the increase in beam accelerating cialized test sample for FESEM has exceeded < I nni (29). For biological samples with limited thickness (up to 50 nm), the determination of resolution, as defined by resolving known structure in biological samples, varies from 1.8-2.5 nm as reported in studies on bacteriophage structure and semi-crystalline macromolec~~les, like the HPI layer found in the cell wall of Dirzococc~~s racliolar-ian (43,44).…”
Section: Cryosem-zizfinitely Thin Sal~zplesmentioning
confidence: 97%
“…Other FESEM studies have utilized variations of ligancl binding in which cells were treated with tannic acid and glutaraldehyde prior to osmication and observation of nuclear pore struct~ire or combinations of tannic acid and ferrocyanide osmium soliltions for examination of intracellular organelles (27,28). Also, Tanaka has described a method of high resolution imaging for FESEM polished carbon substrates and heavy metal impregnation (phosphotungstic acid, uranyl acetate, and OSIII~LIII~ mordanted by tannic acid) for the successf~~l imaging of macromolec~~les, such as hemocyanin, apoferritin, thyroglobulin, irnm~~noglobulins G and M, and both bacteriophage and cellular organelles including ribosomes (29,30).…”
Section: Advances In Field Emission Sem Low Voltage Sem Of Biologicalmentioning
confidence: 99%